Effects of pilates training on the flexibility and strength of female students - Merisa Tanphukwan; Kritpech Nontakhod; Butsakorn Khongnam; Supitchaya Wongsurin; Jariyawadee Buathong; Pannathon Pakkaro; Kampeeraphab Intanoo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Pilates training is an effective form of exercise for improving flexibility and strength. However, only a few studies have focused on female students.